Penguatan Literasi Santri melalui Pendekatan Service Learning: Studi Kasus pada MA Al Muttaqien Pancasila Sakti - Triningsih; Farida Nur Hidayah; Ajrun 'Azhim Al As'hal (Perpustakaan Universitas Gadjah Mada, 2026)
This study aims to examine the implementation of a service learning-based literacy program in improving the reading and writing abilities of students at MA Al Muttaqien Pancasila Sakti. The program was designed to address low reading interest, limited library resources, and the absence of a structured literacy program. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews using purposive sampling. The informants consisted of 3 teachers, 1 headmaster, 8 students, along with participant observation and documentation of activities. The service learning model was implemented through four stages: needs identification, collaborative program design with teachers, literacy workshop implementation, and reflective evaluation. The findings indicate that service learning strengthens student engagement in literacy practices, improves writing confidence, and fosters collaborative learning. The program resulted in the publication of a student anthology as well as the development of digital literacy practices through digital reading platforms and technology-based reading corners. This study confirms that service learning is an effective pedagogical strategy for building a sustainable literacy culture in Islamic educational settings. The main contribution of this research is the enrichment of the literature on literacy development in Islamic boarding schools (pesantren) and the potential of community-engaged pedagogy.